Transformational Leadership On Employee Innovative Work Behavior: The Role Of Knowledge Sharing Behavior (Jurnal Manajemen Bisnis, 2024)
This article discusses direct influence testing of transformational leadership on employees innovative work behavior and the role of knowledge sharing behavior as a mediating variable. The study encompasses 115 participants from the Semarang City Health Service, and the data analysis was carried out using SEM-PLS with SmartPLS version 3 software. The results indicated a significant effect of TL on IWB and KSB. Another noteworthy finding revealed that KSB had a significant impact on IWB. Moreover, the study identified that TL and IWB can be partially mediated by KSB. The study holds both theoretical and practical implications.